Tkachenko V. I. The giant of Ukrainian literature as a strong defender for the mother language - Tkachenko V. I. (Philological Treatises, 2020)
This article deals with memories of Mykola Lukash that complement the image of this magician of Ukrainian translation. Good examples confirm that Mykola Lucash due to his translation and scientific works has created the most favorable conditions for national revival. And his role in the Ukrainian culture will grow over time based on intellectual development and spiritual growth of the Ukrainian people. Also the author expresses his own understanding of current state of the literary process in Ukraine, especially in translation work.